Assessing the potential of dual-purpose maize in southern Africa: A multi-level approach - Homann-Kee Tui, Sabine; Blümmel, Michael; Valbuena, Diego; Chirima, A.; Masikati, Patricia; Rooyen, Andre F. van; Kassie, Girma T. (Elsevier, 2013)
This paper explores the potential and challenges of increasing production of food and feed on existing maize fields in mixed crop-livestock systems in the semi-arid areas of southern Africa. It integrates results from different sources of data and analysis: 1. Spatial stratification using secondary data for GIS layers: Maize mega-environments combined with recommendation domains for dual-purpose maize were constructed for Malawi, Mozambique and Zimbabwe, stratifying the countries by demand factors (livestock densities and human population densities) and feed availability. Relative biomass contributions to feed resources from rangelands were compared to those from croplands to explore the usefulness of global datasets for feed supply estimations. 2. Verification through farming systems analysis: the potential demand for maize residues as feed (maize cropping patterns, maize yields and uses, feed deficits) was compared at contrasting sites, based on household survey data collected on 480 households in 2010. 3. Maize cultivar analysis: Genotypic variability of maize cultivars was compared to evaluate the potential contribution (stover quantity and quality) of dual-purpose maize to reduce feed deficits. The study results illustrate high spatial variability in the demand for and supply of maize residues. Northern Malawi is characterized by high livestock density, high human population density and high feed availability. Farmers achieve maize yields of more than 2 t/ha resulting in surplus of residues. Although livestock is important, southwest Zimbabwe has low livestock densities, low human populations and low feed availability; farming systems are more integrated and farmers make greater use of maize residues to address feed shortages. Central Mozambique also has low cattle densities, low human populations and low feed availability. More rangelands are available but maize yields are very low and livestock face severe feed shortages. The investigation of 14 advanced CIMMYT maize landraces cultivars and 15 advanced hybrids revealed significant variations in grain and stover yield and fodder quality traits. Where livestock densities are high and alternative feed resources are insufficient, maize cultivars with superior residue yield and fodder quality can have substantial impact on livestock productivity. Cultivars at the higher end of the quality range can provide sufficient energy for providing livestock maintenance requirements and support about 200 g of live weight gain daily. Maize cultivars can be targeted according to primary constraints of demand domains for either stover quantity or stover fodder quality and the paper proposes an approach for this based on voluntary feed intake estimates for maize stover.